Selección objetiva de la progenie en ovinos manchego para carne en Los Llanos de la Rioja - Ricarte, Ramon Armando; Diaz, Raul Fernando; Maizon, Daniel Omar; Brunello, Gabriela Esther; Guzman, Luis Miguel; Vera, Tomas Anibal; Andrada, Magdalena Hilda (Asociación Argentina de Producción Animal (AAPA), 2025)
Ponencia y poster